Levistilide a Induces Ferroptosis by Activating the Nrf2/HO-1 Signaling Pathway in Breast Cancer Cells - Jing S; Lu Y; Zhang J; Ren Y; Mo Y; Liu D; Duan L; Yuan Z; Wang C; Wang Q (Dove Medical Press, 2022)
Shangwen Jing,1,* Yantong Lu,1,2,* Jing Zhang,1 Yan Ren,1,2 Yousheng Mo,3 Dongdong Liu,3 Lining Duan,4 Zhongyu Yuan,5 Changjun Wang,2 Qi Wang1 1Science and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 2Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangdong Geriatric Institute, Guangzhou, People's Republic of China; 3The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 4The First Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 5Department of Medical Oncology, Sun Yat-Sen University Cancer Center, the State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangzhou, 510060, People's Republic of China*These authors contributed equally to this workCorrespondence: Changjun Wang; Qi Wang, Email gzwchj@126.com; wangqi@gzucm.edu.cnIntroduction: Breast cancer (BC) is the leading female malignancy, with one million new cases diagnosed worldwide per year. However, the current treatment options for BC patients have difficulty achieving satisfactory efficacy. Ferroptosis is a new mode of regulated cell death that plays a key role in the inhibition of tumorigenesis. Levistilide A (LA), as an active compound extracted from Chuanxiong Rhizoma, might prevent the development of tumors by regulating the critical cellular processes of ferroptosis.Methods: In this study, the underlying mechanisms of LA on ferroptosis in BC were explored in vitro. The effect of LA on the viability and mitochondrial function of BC cells was determined. Moreover, the effect of LA on the expression levels of key molecules involved in ferroptosis and the nuclear factor erythroid-2-related factor 2/heme oxygenase 1 (Nrf2/HO-1) signaling pathway was evaluated.Results: LA significantly reduced cell viability and damaged the mitochondrial structure and function of BC cells in a dose-dependent manner. Furthermore, LA treatment markedly enhanced reactive oxygen species (ROS)-induced ferroptosis by activating the Nrf2/HO-1 signaling pathway.Conclusion: These findings suggest that LA may be a potential lead compound for breast cancer therapy by inducing ferroptosis in tumor cells.Keywords: breast cancer, levistilide A, ferroptosis, Nrf2/HO-1 signaling pathway